2016
DOI: 10.5301/uro.5000198
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Percutaneous Nephrolithotomy with Adult Standard Size Instruments in Children under 3 Years of Age: A 10 Years Single-Center Experience

Abstract: Due to our experience, utilizing PCNL with adult-sized instruments in management of urolithiasis in less than 3 years old children appeared to be effective and relatively safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Complications rate of 10% to 36.3% had been reported by other studies, which included minor complications in (8%-20%) versus severe complications in (2%-16%) of patients. 12,13 Predictors of complications were studied by a previous multicenter retrospective analysis. That study reported that the operative time, sheath size, mid calyceal puncture, and partial staghorn stones were statistically significant parameters affecting the complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Complications rate of 10% to 36.3% had been reported by other studies, which included minor complications in (8%-20%) versus severe complications in (2%-16%) of patients. 12,13 Predictors of complications were studied by a previous multicenter retrospective analysis. That study reported that the operative time, sheath size, mid calyceal puncture, and partial staghorn stones were statistically significant parameters affecting the complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, as success rates have increased and particular experience has been gained in adults, the technique has also begun to be performed in children as monotherapy, or in combination with other approaches in patients with large stone burdens. Concerns about long-term renal damage, small kidney size, relatively big tools, radiation exposure, and danger of significant problems, such as hemorrhage, contributed to the technique's slow adoption in children [ 48 , 49 ].…”
Section: Pnlmentioning
confidence: 99%